Knowledge, attitude and practice of pharmacy professionals towards PVPI programme - Aleena Alex; Suja Abraham; Heera George (International Journal of Pharmacy and Analytical Research, 2022)
Pharmacovigilance is the pharmacological science relating to the detection, assessment, understanding and prevention of adverse effects, particularly long term and short term side effects of medicines. By giving importance for patient safety, India setup a surveillance system “Pharmacovigilance Programme of India” (PvPI). This work was done mainly to highlight the role of pharmacist in detecting, assessing and documenting adverse drug reactions and also to assess the knowledge, attitude and practice of working pharmacist towards pharmacovigilance programme. A survey was done among 20 working pharmacists and found that 90% of pharmacists were aware of pharmacovigilance and 55% had knowledge about the procedures for reporting ADR. Moreover 95% of them felt that ADR reporting is the responsibility of pharmacist. There are many discouraging factor for ADR reporting, the major barrier was lack of time (40%) and the lack of knowledge about the procedure for reporting (20%). So it is the high time to provide sufficient training and conduct workshop on pharmacovigilance for those working in community or hospital pharmacy in order to uplift the profession of pharmacy into great heights.